Critical success factors of Public-Private Partnerships in the education sector - Sajida; Bevaola Kusumasari (Public Administration and Policy, 2023)
Purpose – This paper aims to identify the factors affecting the implementation of Public-Private Partnerships (PPPs) in the education sector. Design/methodology/approach – Based on Scopus and adopting the protocol of Staples and Niazi (2007), this systematic literature review examined 21 articles on PPPs in the education sector. Content analysis is adopted to identify research gaps and provide information on critical issues in the cases. Findings – The findings have identified the critical success factors of PPPs in the education sector in 12 countries, revealing varying degrees of success and implementation challenges. They reflect the importance of clear objectives, effective communication, and robust partnerships between the public and private sectors to achieve success. These insights contribute to an in-depth understanding of PPP implementation in education, which can guide future projects. Originality/value – The critical success factors identified in PPPs implementation in education across various countries may provide a comprehensive worldwide perspective for researchers, practitioners and policymakers.